(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to find out "The Influence of Risk, Ease, Trust, on Customers’ Interests Using BRImo BRI Mobile Banking PT. Bank Rakyat Indonesia (Persero), Tbk Cimahi Branch", the unit of analysis is the BRI bank customer of Cimahi branch. Referring to the purpose of the study, the authors chose the Descriptive and Verificative which are research methods with the aim of testing hypotheses that have been formulated previously (research testing). In this method, there was still a descriptive explanation, but the focus lay in explaining the relationship between variables (associative). Can be calculated the sample size of the BRI Bank customer population in December 2019 as many as 358,546 customers. Sources of data in this study are primary and secondary data. Primary data were obtained through measurement of perception and for this purpose the instrument was prepared in the form of a questionnaire containing questions and/or statements using a Likert scale. While secondary data was obtained through literature studies related to risk, convenience, customer trust and interest in using. Hierarchical Regression Analysis, sample distribution of 100, T-test and F-test for the research model.